Performance modeling of projects with multi-variate input and an output using data envelopment analysis - Ku-Mahamud, Ku Ruhana; Ahmad, Faudziah; Mat Kasim, Maznah; Abd Ghani, Nor Farzana; Abdullah, Fader (2012)
Current efficiency models have not been used to measure the efficiency of projects conducted within an organization. Hence, the study aims to develop an efficiency model based on projects undertaken within an organization using non-parametric approach, specifically, data envelopment analysis. In-Fusion Solutions Sdn. Bhd. (ISSB) was chosen as the case study and data were collected from primary and secondary sources.Primary data were obtained through interviews conducted with personnel from the main office and the company branch in Chennai, India.Secondary data were obtained from published and unpublished documents, consisting of thirty-nine completed projects.The data used were of three inputs and an output namely, labor cost, material cost, project duration, and project contract value, respectively. The experimental result was able to identify efficient and inefficient projects.The results obtained showed that three (3) of the projects were efficient, while the remaining projects were not. Improvements for the inefficient projects were suggested based on input and output orientation.